UNDERSTANDING THE POWER OF NEW LITERACIES THROUGH VIDEO GAME PLAY AND DESIGN - Sanford, Kathy; Madill, Leanna (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
In this article, we provide the results of our examination of the range of multiliteracy activities that engage boys’ time and attention, and the types of literacy skills and understandings they learn through their engagement with alternative texts. We focus particularly on video game play and creation/composition as a learning activity that consumes a great deal of their out‐of‐school time. Our observations and conversations with adolescent boys suggest that significant, powerful learning is happening through video game play and creation, and calls into question claims that boys are not succeeding at literacy, instead suggesting the potential for critical engagement with new literacies. Key words: multiliteracies, technology, video games, composing, alternative texts Dans cet article, les auteures présentent les résultats de leur analyse d’un vaste éventail d’activités de multilittératie auxquelles se consacrent les garçons à l’adolescence et des types d’aptitudes et compréhensions qu’ils apprennent à maîtriser au moyen de textes alternatifs. Les auteures se sont penchées tout particulièrement sur les jeux vidéo et la création/composition comme activité d’apprentissage occupant une très grande partie des heures passées en dehors de l’école. Leurs observations et les conversations qu’elles ont eues avec des garçons semblent indiquer qu’un apprentissage important a lieu à travers les jeux vidéo et leur création, ce qui remet en question l’affirmation selon laquelle les garçons ont des lacunes en littératie et suggère plutôt que les nouvelles littératies offrent un potentiel sur lequel il y a lieu de réfléchir. Mots clés : multilittératies, technologie, jeux vidéo, composition, textes alternatifs